2007
DOI: 10.1111/j.1365-2672.2007.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of thermophilic populations during thermophilic aerobic digestion of potato peel slurry

Abstract: To study the diversity of thermophiles during thermophilic aerobic digestion (TAD) of agro-food waste slurries under conditions similar to full-scale processes. Population diversity and development in TAD were studied by standard microbiological techniques and the processes monitored by standard fermentation procedures. Facultative thermophiles were identified as Bacillus coagulans and B. licheniformis, while obligate thermophiles were identified as B. stearothermophilus. They developed rapidly to peaks of 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Further encouragement came from some other studies, which indicate that bacteria of the genus Bacillus are frequently identified in mixed cultures used for the aerobic biodegradation of highstrength industrial effluents at elevated temperature (Lim et al, 2001;Ugwuanyi et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Further encouragement came from some other studies, which indicate that bacteria of the genus Bacillus are frequently identified in mixed cultures used for the aerobic biodegradation of highstrength industrial effluents at elevated temperature (Lim et al, 2001;Ugwuanyi et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, its protective effect against carbon tetrachloride-induced liver injury in rats has been identified (Singh and Rajini, 2008). While banana peel and citrus have been used as media for microbial biomass (Essien et al, 2005) or for enzyme production by fungi (Mamma et al, 2008), most of the by-products from the potato industry are used in animal feed with a combination of other crops (Radunz et al, 2003) or microbial digestion (Ugwuanyi et al, 2008). Plans are being made to use more of the by-products from potato processing.…”
Section: Introductionmentioning
confidence: 99%
“…strains, many of which can be isolated from extreme environments such as deep oil wells and the optimal growth of which is 50–60°C. Additionally, these bacteria are reported as able to heat their own culture up to 50–55°C [16]. The perfect candidate for MTC should meet the following criteria: (i) thermoresistant; (ii) strong exothermic ability; (iii) rapid and easy growth; and (iv) an ability to grow and degrade high concentrations of carbon sources.…”
Section: Discussionmentioning
confidence: 99%